El cantar fúnebre atribuido al Inca Yupanqui. Estudio semántico - Ballón, Enrique (2008)
The chroniclers of the Spanish conquest of the Andes gathered in their texts some traces of the colonized people’s ancestral oral tradition. Thus, Juan de Betanzos included in his Suma y narración de los incas ([¿1551?] 1987) a funeral chant ascribed to Tupac Inca Yupanqui. In this article, I present a semantic and semiolinguistic interpretation of this chant.